Women achieve peak swim performance in individual medley at earlier ages than men - Buhl, C.; Knechtle, B.; Rüst, C. A.; Rosemann, T.; Lepers, R. (Medicina Sportiva, 2013)
Introduction: Previous studies suggested that the age of peak swim performance in freestyle swimming was ~17 years for women and ~19 years for men. However, no study investigated the age of peak swim performance in other disciplines such as individual medley. Objective: To examine the change in the age of peak individual medley performance for both elite female and male Swiss swimmers from 1994 to 2011. Methods: The change in age of peak individual medley performance was investigated for elite female and male swimmers from 1994 to 2011. For comparison, an analysis of freestyle swimming was also performed. Swim speed in 200m and 400m medley, sex and age of the top ten swimmers at national level (Switzerland) were analysed using linear regression and two-way analysis of variance (ANOVA). Results: The age of peak swim speed was (P < 0.01) higher for men than for women in 200m medley (21.1 ± 1.0 vs 18.2 ± 0.8 years) and in 200m freestyle (21.4 ± 0.9 vs 19.3 ± 1.0 years). The age of peak swim speed was (P < 0.01) higher for men than for women in 400m medley (20.8 ± 0.4 vs 18.6 ± 0.7 years) and in 400m freestyle (20.3 ± 1.0 vs 18.6 ± 1.5 years). The age of peak swim speed remained unchanged across years for both medley and freestyle (P > 0.05). Swim performances improved for both swim styles and distances across years (P = 0.03). Conclusion: The age of peak swim performance in medley and freestyle remained stable and was lower for women than for men in elite Swiss swimmers during the 1994 to 2011 period. Future studies need to investigate the age of peak swim speed in swimmers at international level in other competitive swim strokes.